COOPERATION AS THE BASIC CATEGORY OF THE INTERACTIVE STUDY - Світлана Наход (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
Article is devoted to the theoretic analysis of the problem of the determination of the cooperation as the basic category of the interactive study. Modern understanding of the cooperation matter in various fields of science has been systematized and analyzed. The structure components and attributes of cooperation have been studied. The main functions of the interaction of the subjects of the pedagogical process have been determined in this paper. It has been clarified, that interactive study is defined by intensified pedagogical cooperation, as well as by pedagogical process participants' interplay through the prism of personal identity, personal experience in vital activity. It has been defined, that the peculiarity of the cooperation in the interactive study is the creation of new knowledge and also it is the search of the new ideas which are the base for the formation of the students' personality.